Differences in Triage Accuracy for Respiratory Emergency Cases between Academic and Professional Level Nursing Students Using the Early Warning System Score (EWSS) - Vita Maryah Ardiyani; Wahyu Dini Metrikayanto; Ani Sutriningsih; Putu Sintya Arlinda; Risna Yekti Mumpuni; Yati Srihayati; Rosly Junaedi; Indah Dwi Pratiwi; Wyssie Ika Sari; Hardiyanto (Journal Of Nursing Practice, 2026)
Background: EWSS functions as a cumulative scoring framework that standardizes the clinical assessment of acute illness severity through systematic evaluation of vital sign measurements. Purpose: EWSS is a simple scoring system utilizing the Track & Trigger method based on patients' vital signs to detect early signs of clinical deterioration. It employs physiological parameters to identify patients with severe infections and facilitate triage decisions based on the severity level. Methods: The objective of this study is to compare the accuracy of triage determination in respiratory emergency cases between two groups of students: academic-level nursing students and professional-level nursing students, using the Early Warning System Score (EWSS) instrument. The research was implemented at nursing undergraduate education institutions in Malang City and Malang Regency. The sample consisted of 100 nursing students, divided into two groups: 50 academic-level students and 50 professional-level students. Each respondent was given 10 respiratory emergency vignette cases and performed triage assessments using the EWSS instrument. Results: The analysis showed that the Mann-Whitney test has a significance value 0.45, indicating no significant difference in triage accuracy using EWSS between academic-level and professional-level students. Almost all respondents were able to accurately determine triage for both groups using the EWSS method. Conclusion: EWSS can be broadly utilized by both academic and professional-level nursing students. The triage instrument based on patients' clinical signs and symptoms, EWSS is expected to be widely adopted, including by the general public.